2020
DOI: 10.1136/bmj.m1923
|View full text |Cite|
|
Sign up to set email alerts
|

Incidence, clinical outcomes, and transmission dynamics of severe coronavirus disease 2019 in California and Washington: prospective cohort study

Abstract: ObjectiveTo understand the epidemiology and burden of severe coronavirus disease 2019 (covid-19) during the first epidemic wave on the west coast of the United States.DesignProspective cohort study.SettingKaiser Permanente integrated healthcare delivery systems serving populations in northern California, southern California, and Washington state.Participants1840 people with a first acute hospital admission for confirmed covid-19 by 22 April 2020, among 9 596 321 healthcare plan enrollees. Analyses of hospital … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
187
3
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(214 citation statements)
references
References 39 publications
(61 reference statements)
16
187
3
4
Order By: Relevance
“…For example, one New York cohort study initially reported a mortality of 88% for patients requiring mechanical ventilation before readers’ responses led to a correction clarifying that the rate was 25% and would grow to an uncertain extent because 72% of patients were still in hospital 4. In contrast, the two linked cohort studies from the United States provide rigorous outcome ascertainment and adjustment for case mix 67. By delaying publication until most enrolled patients had confirmed outcomes and by using modern survival analysis methods these authors have greatly enhanced our understanding of the epidemiology of covid-19.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, one New York cohort study initially reported a mortality of 88% for patients requiring mechanical ventilation before readers’ responses led to a correction clarifying that the rate was 25% and would grow to an uncertain extent because 72% of patients were still in hospital 4. In contrast, the two linked cohort studies from the United States provide rigorous outcome ascertainment and adjustment for case mix 67. By delaying publication until most enrolled patients had confirmed outcomes and by using modern survival analysis methods these authors have greatly enhanced our understanding of the epidemiology of covid-19.…”
mentioning
confidence: 99%
“…Lewnard and colleagues (doi:10.1136/bmj.m1923) report on 1840 people with covid-19 at Kaiser Permanente system hospitals in California and Washington state 6. Median age was 61 years with 25% being 48 years or younger.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Independent risk factors for death included black and Asian ethnicity (versus white ethnicity) and deprivation, similar to findings from the United States 11. An integrated health delivery plan in California and Washington states has used data from 9.6 million enrollees in a study that reported 1277 hospital admissions and 15% mortality in hospital to examine community transmission dynamics 12…”
mentioning
confidence: 76%
“…patients from California and Washington. 48 Over 50% of patients were with a length of hospital stay of 20 days or more. 49 Immunomodulatory agents remain a promising strategy for the treatment of severe COVID-19, since it can attenuate the increased in ammatory response of the patients.…”
Section: Discussionmentioning
confidence: 99%